Metachronous rectal metastasis from pulmonary adenocarcinoma after 11 years of chemo-, immuno-, and radiotherapy for recurrent lesions: a case report - Yozo Suzuki; Mitsunobu Imasato; Yujiro Nakahara; Atsushi Naito; Manabu Mikamori; Masahisa Ohtsuka; Kenta Furukawa; Jeong Ho Moon; Tadafumi Asaoka; Kentaro Kishi; Hironao Yasuoka; Kiyoshi Komuta; et al. (Surgical Case Reports)
Abstract Background Rectal metastasis from pulmonary adenocarcinoma is rare, and it has been regarded as an end-stage phenomenon. Recently, however, advances in lung cancer treatment have improved the chance of long-term survival of patients with unresectable distant metastases. We describe the occurrence and management of metastatic spread of a pulmonary carcinoma to the rectum. Case presentation The patient was a 79-year-old woman who had undergone thoracoscopic left lobectomy for pulmonary adenocarcinoma and then, over the next 11 years, various drugs (carboplatin + paclitaxel (as adjuvant therapy), gefitinib, gemcitabine + vinorelbine, S1 (an oral 5-fluorouracil-based drug), carboplatin + pemetrexed + bevacizumab, erlotinib, nivolumab, afatinib, and carboplatin+ S1) were administered, especially for hilar and mediastinal lymph node recurrences. During the eleventh postoperative year, left and right iliac bone metastases were detected, and radiation therapy was undertaken for local control of these lesions. When 18F-fluorodeoxyglucose positron emission tomography was performed for evaluation of the disease, tracer accumulation in the upper rectum was seen. Colonoscopic examination of the rectum revealed an intramural mass with central ulceration, and the mass was diagnosed histologically as an adenocarcinoma. The bone metastases appeared to be controlled, and the patient’s performance status was good, but she had suffered constipation for about a year and desired treatment. Thus, laparoscopic low anterior resection was performed. Histopathologic analysis revealed a moderately differentiated adenocarcinoma existing mainly between the submucosa and serosa, and immunohistochemical analysis showed the tumor to be positive for cytokeratin (CK) 7, negative for CK20, positive for thyroid transcription factor-1, and negative for special AT-rich sequence-binding protein 2 and caudal type homeobox 2, confirming the diagnosis of rectal metastasis from the primary pulmonary adenocarcinoma. The patient recovered well without any change in her functional status. Systemic chemotherapy was resumed, and she continues to do well, now 6 months after surgery. Conclusions Surgery may be a good option for the management of an isolated rectal metastasis from pulmonary cancer in patients whose functional status is good.